Enhancing reading comprehension skills among Bhutanese English learners through translanguaging - Thinley Wangdi; Amit Rai (Studies in English Language and Education)
Translanguaging has recently emerged as a prominent field of study. Despite its growing popularity, its impact on students’ reading comprehension skills remains largely unexplored. This study employed a quasi-experimental research design to examine the impact of translanguaging on students’ reading comprehension performance. The study also examined students’ perceptions of translanguaging to gain a deeper understanding of translanguaging’s potential impact. Data were gathered through pre-and post-tests, questionnaires, semi-structured interviews, and observations. A sample of 56 Bhutanese school students (33 males, 23 females) were purposely recruited and divided into two groups: the experimental and control groups. The experimental group was taught using the translanguaging approach, while the control group followed a monolingual approach. The findings, based on the comparison of pre-and post-test scores between the two groups, revealed that the translanguaging group significantly outperformed the monolingual group in their post-test scores despite a negligible difference in pre-test scores. This suggests that translanguaging could be an effective teaching approach to enhancing students’ reading comprehension skills. Furthermore, despite the dominant position of English as a Medium of Instruction (EMI) in the context, most students perceived translanguaging as an effective pedagogical practice. They reported that it allowed them to freely use their language repertoire to discuss and learn new vocabulary and difficult content, improved their confidence to participate in classroom discussions, and enhanced lesson comprehension. This study concludes with practical implications and suggestions for future research.